Entrepreneurial Management and its Place in the Competition Economy - VĂCĂRESCU HOBEANU, Loredana (Journal of Advanced Research in Management; Vol 8 No 1 (2017): JARM Volume VIII Issue 1(15) Summer 2017, 2017)
Like any other type of company, the performances of the Small and Medium-sized Enterprises (SMEs) depend on the effective appeal and implementation of concepts, approaches, methods, techniques and other elements which are provided by the management science. Moreover, being given the pronounced, constructive and functional specificity of the SMEs, they require a specific management, being named entrepreneurial management. Relatively young branch of the management, the entrepreneurial management, still ongoing crystallization, is desired increasingly conditioned for the performances of the SMEs. The typical entrepreneurial activities, to which there are devoted 99% of the researches and studies, are the economic activities. The entrepreneurial activity is in the centre of economic innovation spirit, productivity growth, economic competitiveness and generating the jobs, this being associated with the personal success. The entrepreneurial activity synthetically consists in the identification and capitalization of an economic opportunity. The entrepreneurial environment consists of all the exogenous company elements of economic, managerial, technical, demographic, cultural, scientific, psychological, educational, political, ecological and legal nature which marks significantly the activities performance and the results achievement.